2016
DOI: 10.4067/s0718-23762016000200009
|View full text |Cite
|
Sign up to set email alerts
|

Building the Concept of Happiness for Adults From Phenomenography

Abstract: There is a growing interest in psychology and social sciences to study happiness. Studies are predominantly of positivist epistemology where the concept typically is charged-ethicextensively, ignoring the meaning of happiness to people. To unravel this, an observational, descriptive, transversal study of phenomenographic approach and the corresponding method-emic-are reported here. A non-random sample of faculty and personal staff of a University consisting of 164 Chilean adults of both sexes responded volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
(11 reference statements)
0
6
0
5
Order By: Relevance
“…The mere presence, particularly of the partner and the children, leads the person to a state of happiness. It is very likely to be related, on the one hand, to the need to be able to count on others in vulnerable cultures to face shortcomings and vicissitudes (earthquakes and other natural disasters, but also inclemency in the work market, or to satisfy health needs), and on the other hand, with the high value given to family in the Latin American culture (Moyano Díaz, 2016b), which is also embedded in some measure with the following dimension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mere presence, particularly of the partner and the children, leads the person to a state of happiness. It is very likely to be related, on the one hand, to the need to be able to count on others in vulnerable cultures to face shortcomings and vicissitudes (earthquakes and other natural disasters, but also inclemency in the work market, or to satisfy health needs), and on the other hand, with the high value given to family in the Latin American culture (Moyano Díaz, 2016b), which is also embedded in some measure with the following dimension.…”
Section: Discussionmentioning
confidence: 99%
“…The fifth dimension refers to having a set of satisfactions or well-beings in different domains or areas of the human functioning: social, psychological, economic, and physical, which are accompanied by emotions of joy and states of tranquility, peace, recognition and hope. It refers to a variety of states or components related to happiness, more than this per se, and which can be considered as influential elements or determinants of happiness (Moyano Díaz, 2016b).…”
mentioning
confidence: 99%
“…Empirical evidence in the case of Latin America and Chile has also shown similar findings (e.g. Hernández-Aburto et al, 2017;Moyano-Díaz, 2016;Moyano Díaz & Ramos Alvarado, 2007). Since this belief is deeply rooted in Latin American folk culture, when anyone in the region see someone who has money, health, and love, they will likely attribute a higher level of happiness than to those individuals without these three things.…”
Section: Causal Attribution Of Happinessmentioning
confidence: 56%
“…Even though this order of priority is a research question of its own and can be answered by our empirical strategy, happiness-income studies have consistently shown they are crucial happiness determinants (Aknin et al, 2009;Böckerman et al, 2014;Kohler et al, 2005;Thaler & Sunstein, 2008). Empirical evidence in the case of Latin America and Chile has also shown similar findings (e.g., Moyano-Díaz, 2016;Hernández et al, 2017;Moyano-Díaz & Ramos, 2007). Since this belief is deeply rooted in Latin American folk culture, when anyone in the region see someone that has money, health and love, they will likely attribute a higher level of happiness than to those individuals without these three things.…”
Section: Causal Attribution Of Happinessmentioning
confidence: 73%